ANALISIS DINAMIK MODEL PENDANGKALAN DANAU LIMBOTO DENGAN PEMBERSIHAN ECENG GONDOK DAN PENGERUKAN ENDAPAN - Mahmud, Sri Lestari; Achmad, Novianita (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2020)
This article discusses about mathematical model of Limboto lake silting with water hyacinth cleaning solution. Modelling begins with constructing a model based on the factors that affect silting which is then formed into a system of first order differential equations. Furthermore, the model is analyzed by looking for equilibrium and stability. To see the condition of lake silting based on the stability condition, a numerical simulation was performed. The simulation results show that with water hyacinth cleaning, the lake will maintain its existence, which is indicated by an increase the Limboto lake volume, although there is still a decrease in volume due to the presence of sediment and nutrients from the river.